Don’t blame the election on fake news. Blame it on the media. - Watts, Duncan J.; Rothschild, David (Columbia Journalism Review, 2017)
Since the 2016 presidential election, an increasingly familiar narrative has emerged concerning the unexpected victory of Donald Trump. Fake news, much of it produced by Russian sources, was amplified on social networks such as Facebook and Twitter, generating millions of views among a segment of the electorate eager to hear stories about Hillary Clinton’s untrustworthiness, unlikeability, and possibly even criminality. “Alt-right” news sites like Breitbart and The Daily Caller supplemented the outright manufactured information with highly slanted and misleading coverage of their own. The continuing fragmentation of the media and the increasing ability of Americans to self-select into like-minded “filter bubbles”...